HUBUNGAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN LOMPAT JAUH MAHASISWA PENJASKESREK STKIP-PGRI LUBUKLINGGAU - Irham Dani; Sukasno Sukasno; Azizil Fikri (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the relationship between limb muscle explosive power and the long jump ability of STKIP-PGRI Lubuklinggau students. This research is a correlational study. The population in this study was the 3rd semester of Physical Education and Health students in the 2020 Academic Year STKIP-PGRI Lubuklinggau. The sample used is 30 students. The research method used is correlation, with data collection techniques using tests and measurements. The instrument for measuring the explosive power of the leg muscles uses the standing broud jump test and for the long jump ability using the long jump test. The data analysis technique uses normality, linearity, and product moment correlation tests using SPSS (Statistical Program For Social Science) for windows software. The results showed that: There was a significant relationship between the explosive power of the leg muscles and the long jump ability of the Physical Education students at STKIP-PGRI Lubuklinggau, with the value of rcount = 0.544 > r table = 0.361. With the contribution of leg muscle explosive power to the long jump ability of the 3rd semester physical education and health sector students in the 2020 Academic Year of STKIP-PGRI Lubuklinggau, amounting to 29.6%. Then the alternative hypothesis is accepted.